Оптоелектронний пристрій на основі транспарантів з повним набором логічних операцій для роботи з матрицями - Лисенко, Г.Л.; Мялківська, І.В.; Дюдюн, О.В. (Оптико-електронні інформаційно-енергетичні технології, 2009)
In given article creation possibility optoelecronic device with a set of logic operations for work with matrixes is considered. The device consists their four layers of operated semiconductor modulators. Thus the device can carry out any of logic operations: AND, OR, the sum on the module 2, NAND, negative OR, negative sum on the module 2.